2013
DOI: 10.5433/1679-0359.2013v34n3p1121
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of noise level emitted by micro tractor in static and dynamic conditions

Abstract: Noise is a complex mixture of sounds that causes the feeling of discomfort and is continuously present in the daily lives of human beings. The objective of this study is to assess the noise level emitted by a micro tractor in various situations. In the first situation, the micro tractor is standing still and is subjected to 600, 800, and 1100 rpm from four positions -right, front, left, and rear sides -as well as four distance radii -1, 2, 5, and 10 m. In the second situation, the micro tractor is in motion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…However, the use of PPE is still recommended for all workers involved in this machine operation. The minimum noise value produced by this tractor was around 73.5 dB (Table 1) observed in point (4, -10), i.e., the farthest from the source, corroborating with results found by Magalhães et al (2012); Pimenta ; Nascimento et al (2013) and Missio et al (2015).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…However, the use of PPE is still recommended for all workers involved in this machine operation. The minimum noise value produced by this tractor was around 73.5 dB (Table 1) observed in point (4, -10), i.e., the farthest from the source, corroborating with results found by Magalhães et al (2012); Pimenta ; Nascimento et al (2013) and Missio et al (2015).…”
Section: Resultssupporting
confidence: 88%
“…Baesso et al (2015) evaluated 12 tractors of different models and concluded that tractors without a closed cabin had noise levels close to the operator's ear above the levels allowed by NR 15, being necessary the use of ear protectors. Studies performed by Rinaldi et al (2008), Alves et al (2011) and Nascimento et al (2013) also concluded that farm machinery noise levels were above tolerance limits, being needed to take measures to reduce or eliminate the risk which the workers were exposed in the agricultural operations.…”
Section: Resultsmentioning
confidence: 99%
“…They found that most of the tractors emitted noises higher than the threshold established in NR 15. Also, Nascimento et al (2013) reported the results of a work with a walking tractor, disclosing that the tractor presented unsatisfactory high levels of noise and, therefore, suggested that the operators of these machines should use personal protective equipment full time.…”
Section: Resultsmentioning
confidence: 99%